The Potential use of Honey as a Remedy for Allergic Diseases: A Mini Review - Aw Yong, Poi Yi; Islam, Fahmida; Harith, Hanis Hazeera; Israf, Daud Ahmad; Tan, Ji Wei; Tham, Chau Ling (Frontiers in Pharmacology, 2021)
Honey has been conventionally consumed as food. However, its therapeutic properties have also gained much attention due to its application as a traditional medicine. Therapeutic properties of honey such as anti-microbial, anti-inflammatory, anti-cancer and wound healing have been widely reported. A number of interesting studies have reported the potential use of honey in the management of allergic diseases. Allergic diseases including anaphylaxis, asthma and atopic dermatitis (AD) are threatening around 20% of the world population. Although allergic reactions are somehow controllable with different drugs such as antihistamines, corticosteroids and mast cell stabilizers, modern dietary changes linked with allergic diseases have prompted studies to assess the preventive and therapeutic merits of dietary nutrients including honey. Many scientific evidences have shown that honey is able to relieve the pathological status and regulate the recruitment of inflammatory cells in cellular and animal models of allergic diseases. Clinically, a few studies demonstrated alleviation of allergic symptoms in patients after application or consumption of honey. Therefore, the objective of this mini review is to discuss the effectiveness of honey as a treatment or preventive approach for various allergic diseases. This mini review will provide insights into the potential use of honey in the management of allergic diseases in clinical settings.